2008
DOI: 10.1111/j.1748-5827.2008.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measurements of 18 analytes in canine and feline blood samples using the in‐practice Falcor 350 and the reference KoneLab 30i analysers

Abstract: For 13 of the 18 analytes (creatinine, total proteins, albumin, creatine kinase, aspartate aminotransferase, alanine aminotransferase, amylase, glucose, cholesterol, triacylglycerol, phosphate, potassium and urea) in both canine and feline samples, the two instruments produce values that are closely related to each other (excellent correlation) and are sufficiently similar to allow them to be used interchangeably without the need for additional correction factor computations (good agreement). Because of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…Examination of the data revealed that in 45 of the 60 cases (75%), the Falcor generated tCa values higher than those of the KoneLab. This finding may reflect the different methodologies employed by the two instruments (Cresolphthalein complexone versus Arsenazo III) and is in agreement with the results reported in an identical study in cats and dogs where in 49 of 60 canine (81%) and 39 of 60 feline (65%) cases the Falcor generated tCa values higher than those of the KoneLab [14]. …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Examination of the data revealed that in 45 of the 60 cases (75%), the Falcor generated tCa values higher than those of the KoneLab. This finding may reflect the different methodologies employed by the two instruments (Cresolphthalein complexone versus Arsenazo III) and is in agreement with the results reported in an identical study in cats and dogs where in 49 of 60 canine (81%) and 39 of 60 feline (65%) cases the Falcor generated tCa values higher than those of the KoneLab [14]. …”
Section: Discussionsupporting
confidence: 88%
“…The reason for the unacceptable correlation observed for Na + is not readily apparent and may merit further investigation. Similar differences in the correlations between the Falcor and KoneLab instruments for Na + and K + values have also been reported in a recent study which utilised samples from 60 canine (Na + ; r = 0.41, K + ; r = 0.96) and 60 feline (Na + ; r = 0.61, K + ; r = 0.97) clinical cases [14]. …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Therefore, possible matrix interference cannot be ruled out. In addition, the bias of Na + (-12.2-11.6 mmol/l) and K + (-0.6 to 0.6 mmol/l) was significantly larger than those reported when wet-reagent analysers (Na + 1.7-0.2; K + 0.4-0.3; Papasouliotis et al 2008) and point-of-care testing portable analysers (Na + 4.5; K + 0.2; West et al 2014) were used. A previous study indicated that when the photometric measurement range (2.5A) is exceeded, then results may be unpredictably low or even negative (Hubl et al 1994).…”
Section: Discussionmentioning
confidence: 51%
“…Correlations between AmiShield and reference instruments were determined by Deming regression using EP Evaluator Release 6 (Data Innovations LLC, South Burlington, USA). The value of Pearson's correlation coefficient was either considered excellent (r ≧ 0.92), good (r = 0.80-0.91), fair (r = 0.59-0.79), or poor (r < 0.59), based on previous studies (Papasouliotis et al 2006;Papasouliotis et al 2008). Data were also plotted on Bland-Altman difference plots to evaluate the degree of agreement between AmiShield and the reference instruments.…”
Section: Methodsmentioning
confidence: 99%